Return to Golf Rehabilitation Progression after Anterior Cruciate Ligament Reconstruction Using an Evidence-Based Foundation - Sean Hazzard; Michael Young; Danielle Lonati; Peter Asnis (International Journal of Sports Physical Therapy, 2026)
Background Golf is commonly regarded as a low-impact sport, yet the golf swing generates multiplanar loads across both knees. No validated return-to-golf protocol after anterior cruciate ligament reconstruction (ACLR) has been published, and general return-to-sport timelines do not address golf-specific swing volume, club progression, lead- versus trail-knee demands, or return-to-course exposure. Purpose The purpose of this clinical commentary is to synthesize the available golf-biomechanics and ACLR-rehabilitation evidence and present an evidence-informed, criteria-based progression from putting through unrestricted course play. Study Design Clinical Commentary/Current Concept Review. Methods A targeted narrative search of PubMed/MEDLINE and reference lists was performed through June 2026 for literature addressing golf and knee biomechanics, golf-swing modifications, ACLR rehabilitation and return-to-sport criteria, and graft healing. Recommendations were classified as direct golf-biomechanics evidence, indirect ACLR-rehabilitation evidence, or author-consensus guidance when direct evidence was unavailable. Results No study prospectively evaluated a staged return-to-golf protocol after ACLR. Available evidence indicates that both knees experience meaningful loading throughout the golf swing, with the lead knee subjected to substantial frontal-plane moments and transverse-plane rotational loading during impact and follow-through, while the trail knee also experiences meaningful loading during the backswing and transition. Longer clubs, greater clubhead speed, and larger or faster pressure shifts may increase loading demands across both lower extremities. A six-phase progression is proposed using universal symptom and range-of-motion requirements, objective strength and movement criteria, prescribed swing volumes, lead- and trail-knee considerations, and a separate return-to-course phase. Conclusion Return to golf after ACLR should be managed as a continuum rather than a single clearance decision. Time from surgery provides a biologic safeguard but should not replace assessment of effusion, pain, motion, gait, strength, movement quality, workload tolerance, and confidence. The proposed protocol is intended to guide clinical decision-making and requires prospective validation. Level of Evidence 5